2008
DOI: 10.1007/s10566-008-9051-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aggression Towards Residential Social Workers: Do Qualifications and Experience Make a Difference?

Abstract: Residential social workers (RSWs), working in children's homes, have been shown to be particularly vulnerable to physical assault and threatening behaviour from those in their care and yet little research has investigated the factors related to such aggression. This quasi-experimental design examined prevalence of aggression across different grades and investigated the extent to which qualifications and training and increased experience in the job might moderate the levels of aggression experienced by virtue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
2
9
0
1
Order By: Relevance
“…In line with other studies, such as Sekol (2014), Alink et al (2014), Euser et al (2014, Harris and Leather (2012) and Winstanley and Hales (2008), our study shows that violence is a common phenomenon within secure units for adolescents. Secure units are challenging work settings where adolescents with a range of problematic behaviour live under the same roof, while staff are often not adequately trained to deal with such behaviour.…”
Section: 'A Challenging and Demanding Work Setting'supporting
confidence: 93%
“…In line with other studies, such as Sekol (2014), Alink et al (2014), Euser et al (2014, Harris and Leather (2012) and Winstanley and Hales (2008), our study shows that violence is a common phenomenon within secure units for adolescents. Secure units are challenging work settings where adolescents with a range of problematic behaviour live under the same roof, while staff are often not adequately trained to deal with such behaviour.…”
Section: 'A Challenging and Demanding Work Setting'supporting
confidence: 93%
“…With such a limited number of studies on the topic, and the critical role that accurate incident reporting has on the prevention of workplace violence (Crilly, Chapman, & Creedy, 2004; Winstanley & Hales, 2008), there is clearly a need for further rigorous research that examines specifically incident reporting of violent or aggressive acts of patients toward health-care providers in noninstitutional health-care settings. In a systematic review of the literature examining patient violence and aggression in noninstitutional health-care settings, Campbell, McCoy, Hoffman, and Burg (2014) found that there are a limited number of published studies with a specific focus on workplace violence in noninstitutionalcare settings such as home health-care agencies.…”
Section: Incident Reporting By Health-care Workers In Noninstitutionamentioning
confidence: 99%
“…It is generally accepted that workplace violence occurs commonly in certain healthcare professions such as nursing, 1 general practice, 1 ' 2 " 5 social work, 6 " 13 and prehospital setting. 14 " 1 Definitions of workplace violence have varied, but for the health sector, can be defined as, "Incidents where staff are abused, threatened, or assaulted in circumstances related to their work, including commuting to and from work, involving an explicit or implicit challenge to their safety, well-being or health".…”
Section: Introductionmentioning
confidence: 99%